Revolutionising Digital Marketing Education with Generative Artificial Intelligence Integration: An Asynchronous Approach - John Bustard; Mihaela Ghisoiu (Proceedings)
The discipline of marketing has seen a significant shift toward the use of AI over the past 10 years, with generative AI such as ChatGPT exponentially accelerating the impact of this technology due to its accessibility and relevance in helping meet organisational and practitioners’ objectives. The objective of this project was to innovatively incorporate generative pretrained transformers (GPTs) into digital marketing education as a means of asynchronously exposing learners to advances in this domain but also provide insights into managing AI use in this field more effectively. This pilot study focused on supporting tourism enterprises in less developed countries (LDCs), specifically Botswana, Uganda, and Zambia.